L’Afrique de l’Est et les réseaux d’échanges océaniques entre les Ier et XVe siècles - Philippe Beaujard (Afriques)
Since the second millennium BC, East Africa has been connected with oceanic exchange networks and has been included within an Afro-Eurasian world-system, where it formed a periphery from the start of the first millennium of the Christian Era, then a semi-periphery from the Xth century onward. As the various articles of this issue of the Journal Afriques show, although the East African coast has been oddly neglected by authors such as K. Chaudhuri (1975) and J. Abu-Lughod (1989), it did play an active role in the world-system even after the arrival of the Portuguese during the XVIth century.